Differences in Municipal Structure in Czech and Slovak Republic with Emphasis on Delegated Powers - Fuka, Jan; Grešová, Lucia; Šatera, Karel (International Business Information Management Association-IBIMA, 2016)
Czech and Slovak Federal Republic on January 1st, 1993 split into the Czech Republic and Slovak Republic. Even though, it can be stated that in the field of public administration, and not only here,the development in both countries shows a number of common features. This fact offers considerable possibilities of comparison and analysis resulting from the determination of the particularities of chosen areas of both independent countries which previously fell under one federal government. This article deals with delegated powers and their performance at the municipal level and in view of the significant scope of this problem it may be useful introduction for subsequent analysis. Structure and applying of delegated powers can also be seen as an important instrument of government policy. On the example of two separated countries, we demonstrate that despite of many benefits which decentralization brings, the scope and the way of performance of transferred competencies remain questioned. The aim of this paper is to outline basic differences in the municipal structure and in performance of delegated powers in both countries and build the foundation for further research in this area.
Rozdíly v obecním uspořádání v České a Slovenské republice s důrazem na přenesenou působnost
Keywords: Czech Republic; delegated powers; public administration; Slovak Republic; Česká republika; přenesená působnost; veřejná správa; Slovenská republika